Can integrating wildlife and livestock enhance ecosystem services in central Kenya?. Issue 6 (26th June 2017) - Allan, Brian F; Tallis, Heather; Chaplin‐Kramer, Rebecca; Huckett, Steven; Kowal, Virginia A; Musengezi, Jessica; Okanga, Sharon; Ostfeld, Richard S; Schieltz, Jennifer; Warui, Charles M; Wood, Spencer A; Keesing, Felicia
Abstract : Because wildlife and livestock compete for grazing resources, biodiversity conservation and livestock ranching typically have been portrayed as conflicting uses of African savannas. Here, we offer an alternative perspective by describing a savanna ecosystem in central Kenya where wildlife and livestock exhibit a suite of potential positive interactions. For example, treating livestock with an acaricide offers the unintended benefit of removing ticks from the landscape, a result that has now been shown to occur at both large and small scales. When humans derive financial benefits both from wildlife (through tourism) and from livestock (through food production), they may achieve greater economic stability than when income is derived solely from one source. The integrated management of wildlife and livestock can simultaneously improve human health and wildlife conservation. Optimization of human and wildlife benefits will require the management of ecological and socioeconomic trade‐offs when conflicts occur between stakeholders.